(untitled) (Academic journal Industrial Machine Building Civil Engineering, 2019)
During the exploitation of equipment and piping systems of sulfuric acid, shale, metallurgical, mining, energy and other industries, the metal of a number of structures directly contacts with sulfur-containing agents at high temperatures. This results in intense corrosion, loosening and saturation of the surface layer of metal with sulfur (elementalor in the form of various compounds, including sulfides, iron, oxides) with a concentration of up to 0.6%. Repair welding of such metal at its partial replacement is connected with the big labor costs caused by necessity of mechanical removal of a surface layer, as without this operation in weld metal by standard electrodes hot cracks, pores and notfusion are formed.